Comparative Efficacy Between Intense Pulsed Light Narrow Spectrum and Broad Spectrum in the Treatment of Post-Acne Erythema (PAE) - Al-Quran L; Li G; Liu Z; Xiong D; Cao X; Xie T (Dove Medical Press, 2023)
Lina Al-Quran,1 Guang Li,2 Zhezhang Liu,1 Dan Xiong,1 Xianwei Cao,1 Ting Xie1 1Department of Dermatology, The First Affiliated Hospital of Nanchang University, Nanchang City, People's Republic of China; 2Department of Dermatology, Dermatology Hospital of Jiangxi Province, Nanchang City, People's Republic of ChinaCorrespondence: Ting Xie, Department of Dermatology, The First Affiliated Hospital of Nanchang University, Nanchang City, People's Republic of China, Tel +8615079120510, Email dnxieting@126.comPurpose: Post-acne erythema (PAE) is one of the most common physical sequelae of acne regression, PAE can resolve spontaneously, but in some patients it may last for years. This study aimed to evaluate the efficacy and safety of narrow and broad spectrum filters of intense pulsed light (IPL) for the treatment of PAE.Patients and Methods: This prospective study evaluated 60 patients with PAE for at least 6 months, assigned equally to three groups: 1st group received narrow-spectrum with vascular filter (530- 650 nm and 900- 1200 nm), 2nd group received broad-spectrum with (560/590- 1200 nm) filters, the appropriate adjustments were made according to patient's skin colour. Every patient received four sessions one month apart. 3rd group is blank control group did not receive any treatment. CAT (CEA (Clinical Erythema Assessment), Area, and Telangiectasia) used to grade clearance of PAE before and after treatment, Investigators Global Assessment (IGA) used to assess the improvement score after the treatment, and Cardiff Acne Disability Index (CADI) used to evaluate the impact of PAE on patients' Quality of Life (QoL). Self-satisfaction scale completed at the follow-up. Adverse events and acne relapse were recorded.Results: A significant decrease of CAT score in vascular group (P< 0.05). IGA scale showed significant improvement after vascular treatment. A significant decrease in CADI (P< 0.05) after vascular treatment. Patient satisfaction was higher in vascular group than control and blank control groups. Acne relapse observed in control and blank control groups (40% and 15%, respectively).10% of patients showed pigmentation, 15% had blisters after 590 nm treatment.Conclusion: IPL vascular filter (530- 650 nm and 900- 1200 nm) have efficacy in the treatment of PAE. CADI score, patient satisfaction, and acne relapse were significantly better after vascular narrow spectrum treatment than broad-spectrum treatment.Keywords: PAE, vascular filter, acne relapse, CADI, IPL